Elite endurance athletes and the ACE I allele--the role of genes in athletic performance - Gayagay, G.; Yu, B.; Hambly, B.; Boston, T.; Hahn, A.; Celermajer, D. S.; Trent, R. J. (Human Genetics, 1998)
Genetic markers that might contribute to the making of an elite athlete have not been identified. Potential candidate genes might be found in the renin-angiotensin pathway, which plays a key role in the regulation of both cardiac and vascular physiology. In this study, DNA polymorphisms derived from the angiotensin converting enzyme (ACE), the angiotensin type 1 receptor (AT1) and the angiotensin type 2 receptor (AT2) were studied in 64 Australian national rowers. Compared with a normal population, the rowers had an excess of the ACE I allele (P<0.02) and the ACE II genotype (P=0.03). The ACE I allele is a genetic marker that might be associated with athletic excellence. It is proposed that the underlying mechanism relates to a healthier cardiovascular system.